(untitled) (Journal of the College of Basic Education, 2020)
The present research aims at identifying the effect of the waiting time strategy on the achievement of rhetoric among fifth-grade female students. To achieve this, the researcher adopted an experimental design with partial control, which is the design of the control group with a post-test. Fifth literary at the National Unity for Girls in Baghdad, by (34) students in the experimental group taught according to the strategy of waiting time and (32) students in the control group, which is taught in the usual way.The researcher has prepared a test consisting of (30) paragraphs of multiple choice type and confirmed the sincerity and stability and psychometric characteristics. Using the T-test of two independent samples, the study found a statistically significant difference between the average scores of students of both research groups and for the experimental group.